PENDAMPINGAN PENYUSUNAN KALENDER EVENT TAHUNAN DESA WISATA BANTARAGUNG - Nurul Rochmah; Mersiana Setiarini; Meri Rusdiani; Try Kurniawan Akhbar; Iwan Setiawan Rofiq (POLITEKNIK LP3I JAKARTA, 2026)
Bantaragung Tourism Village has extraordinary natural and cultural attractions, but the management of its tourism agenda is not well structured, so tourist visits are still seasonal. This community service activity aims to assist the managers of Bantaragung Tourism Village (Pokdarwis) in preparing an annual calendar of events as an integrated marketing strategy and to increase tourist visits. The method used in this mentoring program is Asset-Based Community Development (ABCD) which is implemented through three stages: (1) mapping the potential of local arts, culture, and traditions, (2) event design and management workshops, and (3) preparation and digitization of the event calendar. The result of this activity is the formation of the Bantaragung Tourism Village Annual Event Calendar that integrates various cultural festivals, nature sports agendas (sport tourism), and local traditional rituals throughout the year. In addition, this activity has succeeded in increasing the understanding and skills of Pokdarwis in planning, packaging, and promoting events independently. The implications of this structured event calendar are expected to provide schedule certainty for tourists, facilitate promotions for external parties, and have a positive impact on improving the local community's economy in a sustainable manner.